Response of strawberry to NPKS on yield in terrace soil - Ahmed, R; Karim, MR; Quddus, MA; Ahmed, S; Siddiky, MA (Bangladesh Journal of Agricultural Research, 2018)
Strawberry (Fragaria X annanassa Duch.) is highly exhaustive and responsive to chemical fertilizers. An experiment on strawberry was conducted in fruits research field of Horticulture Research Centre, BARI, Gazipur over three consecutive years, 2009-2010, 2010-2011 and 2011-2012 to find out the suitable combination of nitrogen (N), phosphorus (P), potassium (K) and sulphur (S) for yield maximization of strawberry. Fourteen treatment combinations were tested in this trial comprising four levels each of N (0, 90, 115 and 140 kg ha-1), P (0, 20, 40 and 60 kg ha-1), K (0, 85, 110 and 135 kg ha-1) and S (0, 15, 25 and 35 kg ha-1) with blanket dose of 4 kg Zn ha-1, 2 kg B ha-1 and 10 t cowdung ha-1. The experiment was set up in randomized completely block design with three replications. Results showed that treatment combination N115P40K110S25 (underscript represent kg ha-1) produced higher strawberry fruit yield (9.59 t ha-1) followed by N90P40K110S25 kg ha-1 and N140P40K110S25 kg ha-1 treatment combinations. The lowest fruit yield (6.05 t ha-1) was found in control (N0P0K0S0) treatment. Therefore, the combination of N115P40K110S25 kg ha-1 may be considered as suitable dose for strawberry cultivation in terrace soils of Bangladesh. Bangladesh J. Agril. Res. 43(1): 89-97, March 2018